2021
DOI: 10.1371/journal.pone.0254946
|View full text |Cite
|
Sign up to set email alerts
|

Performance of an affordable urine self-sampling method for human papillomavirus detection in Mexican women

Abstract: Introduction Urine self-sampling for human papillomavirus (HPV)-based cervical cancer screening is a non-invasive method that offers several logistical advantages and high acceptability, reducing barriers related to low screening coverage. This study developed and evaluated the performance of a low-cost urine self-sampling method for HPV-testing and explored the acceptability and feasibility of potential implementation of this alternative in routine screening. Methods A series of sequential laboratory assays… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 22 publications
0
24
0
Order By: Relevance
“…Our study confirms that HPV DNA can be detected in first void urine as reported by several studies. However, different results have been reported [ 12 , 13 , 16 , 17 , 23 , 24 ]. In this study, we found substantial agreement between first void urine and clinician-collected cervical samples with prevalence of 34% (95% CI 24%–43.9%) for both samples, and infections with hrHPV types classified as ‘Other hrHPV types’ by the GeneXpert platform being more common.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our study confirms that HPV DNA can be detected in first void urine as reported by several studies. However, different results have been reported [ 12 , 13 , 16 , 17 , 23 , 24 ]. In this study, we found substantial agreement between first void urine and clinician-collected cervical samples with prevalence of 34% (95% CI 24%–43.9%) for both samples, and infections with hrHPV types classified as ‘Other hrHPV types’ by the GeneXpert platform being more common.…”
Section: Discussionmentioning
confidence: 99%
“…A clinically validated and highly sensitive HPV assay (GeneXpert) was used, and urine samples were tested with blinding of cervical results. We used an affordable urine collection container and preservative that is more practical in low-resource settings as reported by Hernandez-Lopez et al [ 23 ]. Most of the previous studies have used specially designed urine collection containers and preservatives that are costly for developing countries [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, it supports the further investigation of the implementation of urine collection as cervical cancer screening method. Another strength of this study is the high response rate (97%) and that urine was collected in basic urine collection cups, which are affordable ( Hernandez-Lopez et al, 2021 ). The main limitation of this study is that the majority of the women had a history of attending cervical cancer screening (n = 104, 74%) and that all women had an abnormal cervical cytology prior to study participation.…”
Section: Discussionmentioning
confidence: 99%